ATTRIBUTABLE CHANGES IN THE CHARACTER OF “MODERN ADVERTISING SYSTEMS” IN THE NEW CENTURY AND INFLUENCED FACTORS - Rustamov , R.R. (Educational Research in Universal Sciences, 2023)
In this article, the authors argue that by the new century, the character of all types of propaganda has fundamentally changed, that propaganda has become a powerful tool used on a global scale for the purpose of various social groups and political forces, and that these changes in the propaganda system are taking place under the influence of a number of social processes, trends, and factors.